The Role Of Arabic Language and Socio Linguistics in Contemporary Period and Sustainable Development in Educational System - Issah Zubairu Achara (PT. Student RIhlah Indonesia, 2026)
Arabic language is a language of the Holy Quran, the Holy Qur’an was revealed in Arabic language, the language of the peoples of paradise, is a unique language by Muslims and non-Muslims over the world. While Linguistics is a scientific study which deals with the language and focus in the area or field of systematic investigation of the properties of a particular language, or is the study of language that deals with syntax semantics morphology, and linguistics involve phonetics, the study of how speech sounds are produced, phonology is the study of sound patterns and changes, morphology, syntax the learning of sentence structure, semantics and pragmatics. Amis and objectives of this article is to create an awareness to the students of Arabic language and Linguistics about the relevance of Arabic languages in contemporary period to also encourage students and parents to show concern about Arabic language and Linguistics, to educate the students of Arabic language about significance of studying Arabic language and linguistics in their society, because without Arabic language someone will not understand the Holy Qur’an, and to advice students to put more efforts in studying Arabic language and linguistics. Problems of the study, among the problems of the study, many students they are running of the study, many students they are running away from the studying Arabic language and Literature, they are running to Islamic studies, they believed that anybody that read Arabic language and Linguistics will not get any job except teaching. Suggestion and recommendation the researcher recommend the following to the students and parents, students should have a relevant Arabic text books, Federal Government should employ a specialist to teach Arabic language and Linguistics.